Ceramic filter tube fiber and preparation method thereof
By using a specific combination of ceramic fiber and silicon carbide, the problem of declining time mechanical performance of ceramic filter pipe fiber fiber fiber fiber, realizing a significant improvement of air perforated rate and bending strength, extending the service life and maintaining high temperature High -intensity performance in the environment.
Patent Information
- Application Number
- CN202311857941.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-12-29
Smart Images

Figure CN117797556B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic fibers, and in particular to a ceramic filter tube fiber and a preparation method thereof. Background Art
[0002] Ceramic fiber filter tube is an efficient and durable filter element made of high-performance ceramic fiber material. It has excellent high temperature resistance, corrosion resistance, and wear resistance, and can be used in harsh environments such as high temperature, high pressure, and corrosion. The structure of the ceramic fiber filter tube is divided into an inner tube and an outer tube. The inner tube is used for filtration, and the outer tube plays a supporting and protective role. The material of the inner tube is ceramic fiber, which has the advantages of uniform pore size, small resistance, and large flux. It can effectively intercept impurities, suspended matter, microorganisms, etc. in the water. The material of the outer tube is mostly stainless steel or alloy steel, which has the characteristics of high strength, corrosion resistance, and high temperature resistance, and can protect the inner tube from erosion and damage from the external environment.
[0003] Ceramic fiber filter tubes are widely used in the fields of chemical industry, environmental protection, energy, etc., such as liquid filtration in the petroleum, chemical, pharmaceutical and other industries, as well as flue gas filtration in the fields of waste incineration and biomass power generation. In these fields, ceramic fiber filter tubes can effectively remove harmful substances in liquids and flue gases, ensuring the environmental protection and safety of the production process.
[0004] For ceramic fiber, its apparent porosity determines its filtering ability. However, when its apparent porosity is larger, its density will decrease due to excessive internal pores. When the volume remains unchanged, its mass will decrease, which will greatly reduce its mechanical properties. In other words, its bending strength will be weakened, thereby shortening the service life of the ceramic filter tube fiber.
[0005] Based on this, the present invention provides a ceramic filter tube fiber, which not only has a high apparent porosity, but also has significantly improved mechanical properties. Summary of the invention
[0006] The purpose of the present invention is to provide a ceramic filter tube fiber and a preparation method thereof to solve the following technical problems:
[0007] How to improve the apparent porosity and mechanical properties of ceramic filter tube fibers.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A ceramic filter tube fiber is composed of the following raw materials in parts by weight: 35-42 parts of alumina fiber, 35-42 parts of silicon oxide fiber, 3-6 parts of polypropylene short fiber, 2-5 parts of carbon black, 2-5 parts of modified silicon carbide, and 5-10 parts of plasticizer.
[0010] The preferred raw material composition is: 37-40 parts of aluminum oxide fiber, 37-40 parts of silicon oxide fiber, 4-6 parts of polypropylene staple fiber, 2-4 parts of carbon black, 3-4 parts of modified silicon carbide, and 6-8 parts of plasticizer.
[0011] More preferably, it is: 38 parts of aluminum oxide fiber, 38 parts of silicon oxide fiber, 5 parts of polypropylene staple fiber, 3 parts of carbon black, 4 parts of modified silicon carbide, and 7 parts of plasticizer.
[0012] The modified silicon carbide is composed of silicon carbide and zirconium boride in a mass ratio of 5:(1-2), preferably in a mass ratio of 5:(1.2-1.8), and more preferably in a mass ratio of 5:1.5.
[0013] In a further embodiment of the present invention, the preparation method of modified silicon carbide is:
[0014] Step 1: Add silicon carbide to dimethylformamide at 55-65°C and stir evenly to obtain a silicon carbide solution, and add sodium hydroxide dropwise to the silicon carbide solution to adjust the pH to 6.8-7.2;
[0015] Step 2: Grind the zirconium boride into powder and add it into the silicon carbide solution with high-speed stirring, and distill it under stirring, and finally grind it into powdery modified silicon carbide.
[0016] Preferably, silicon carbide is ground into particles of 100-200 nm before adding dimethylformamide to facilitate better dispersion and subsequent combination with zirconium boride.
[0017] Silicon carbide is a colorless and transparent crystal. The crystal structure of silicon carbide is divided into hexagonal or rhombohedral α-SiC and cubic β-SiC. It has stable chemical properties, high thermal conductivity, small thermal expansion coefficient and good wear resistance. Zirconium boride is a hexagonal crystal expansion material with high melting point, high hardness, low density, good mechanical properties and high temperature resistance. It can be used to enhance the performance of silicon carbide after being processed and mixed with silicon carbide. However, the oxidation resistance of zirconium boride at high temperature is unstable. When the temperature is less than 1100℃, zirconium boride will form a liquid boron trioxide film on the outside after oxidation, and the inside of the film is porous. of zirconium dioxide, so it has strong antioxidant properties, but when the temperature continues to rise, the zirconium oxide forming the film will evaporate outward, and the film will gradually become thinner until it disappears. At this time, the internal zirconium dioxide will be exposed to the outside and quickly oxidized, resulting in a significant decrease in performance; after zirconium boride is combined with silicon carbide, the crystal plane of zirconium boride and the crystal plane of silicon carbide are adsorbed together. Since the amount of silicon carbide used is more than the amount of zirconium boride, silicon carbide crystals are adsorbed on multiple crystal planes of a zirconium boride crystal. In other words, silicon carbide will not completely surround multiple faces of zirconium boride, thereby forming a modified silicon carbide filled with zirconium boride.
[0018] Therefore, when the tube blank needs to be calcined during the process of preparing ceramic filter tubes, silicon carbide is first oxidized on the surface of zirconium boride to form a glass film. As the temperature rises, the glass film spreads to the surrounding under the action of ductility. At this time, the edges of the glass film formed by multiple silicon carbide crystals on the zirconium boride crystal surface are connected to each other, thereby forming a completely closed glass film sealing layer. At this time, zirconium oxide is isolated inside the glass film sealing layer, and will not contact the external environment even if the calcination temperature reaches above 1100°C. Therefore, it can avoid being oxidized, thereby retaining its performance. Therefore, the modified silicon carbide can still have high-strength mechanical properties under harsh high-temperature environments.
[0019] In a further embodiment of the present invention: in the first step, the usage ratio of silicon carbide to dimethylamide is 1 g:(3-5) ml, preferably 1 g:(4-5) ml, and more preferably 1 g:5 ml.
[0020] In a further embodiment of the present invention: in the second step, the stirring rate of high-speed stirring is 1500-2000 r / min, and the stirring time is 1.5-2 h, preferably the stirring rate is 1700-1900 r / min, and the stirring time is 1.6-1.9 h, and more preferably 1800 r / min, and the stirring time is 1.8 h.
[0021] Under high-speed stirring, the silicon carbide particles and the zirconium boride are evenly dispersed, so that the silicon carbide particles can be more evenly distributed around the zirconium boride particles and combined with them.
[0022] In a further embodiment of the present invention: in the second step, the distillation temperature is controlled at 150-170°C, preferably 155-165°C, more preferably 160°C.
[0023] The dimethylformamide solution can be discharged through distillation to improve the purity of the modified silicon carbide.
[0024] In a further embodiment of the present invention, the plasticizer is a mixture of one or more of paraffin, dibutyl phthalate, and triethyl citrate, preferably paraffin.
[0025] A method for preparing the ceramic filter tube fiber as above is carried out in the following steps:
[0026] S1: mixing carbon black and polypropylene short fibers uniformly under high-speed stirring to obtain carbon black-polypropylene short fibers, adding the carbon black-polypropylene short fibers and alumina fibers into a ball mill, and then adding anhydrous ethanol into the ball mill to mix the materials to obtain mixed fibers;
[0027] S2: Add modified silicon carbide to the mixed fiber and mix evenly, then heat and evaporate to dryness and grind to obtain fiber powder, add plasticizer to the fiber powder and stir evenly at 80-100° C. to obtain ceramic filter tube fiber.
[0028] Since carbon black has self-aggregation properties, carbon black is first mixed with polypropylene staple fibers. The porous structure of polypropylene staple fibers provides them with a larger surface area, increasing the chance of contact with carbon black particles. When carbon black particles come into contact with polypropylene fibers, due to the high surface energy of carbon black, they are easily attached to the fiber surface. At the same time, the polar groups on the surface of polypropylene fibers can interact with the polar groups of carbon black particles to form hydrogen bonds or van der Waals forces, thereby firmly adsorbing the carbon black on the fiber surface. This adsorption allows the polypropylene staple fibers to form a wrapping layer around the carbon black particles. On the one hand, it can improve the binding force between the polypropylene fibers and the carbon black molecules. On the other hand, it is beneficial to disperse the carbon black molecules and avoid the problem of self-aggregation of carbon black molecules causing agglomeration. The chemical resistance, wear resistance, high temperature resistance, oxidation resistance and gas phase stability of carbon black itself can be fully exerted under the carrier of polypropylene staple fibers.
[0029] At the same time, alumina fibers and silica fibers are polycrystalline inorganic fibers, and polypropylene staple fibers are organic fibers with orderly arranged molecular chains. After alumina fibers, silica fibers and polypropylene fibers are mixed, alumina fibers and silica fibers are staggered, and polypropylene fibers are inserted in the gaps between alumina fibers and silica fibers. During high-temperature sintering, alumina fibers and silica fibers expand first, and then shrink during cooling, while polypropylene fibers are burned out, thereby generating multiple interconnected pores. The carbon black inside the pores adheres to the inner walls of the pores after the polypropylene staple fibers are burned out, thereby enhancing the adsorption effect of the pores.
[0030] In a further embodiment of the present invention: in step S1, carbon black and polypropylene staple fibers are stirred at a rotation speed of 2000-2500 r / min for 20-30 min to obtain carbon black-polypropylene staple fibers, preferably 2200-2400 r / min, 23-28 min, and more preferably 2300 r / min, 25 min.
[0031] In a further embodiment of the present invention: in step S1, the mass ratio of balls to materials in the ball mill is 1:(1.5-2), and the mixing time is 6-7h, preferably 1:1.8, 6.5h.
[0032] In a further embodiment of the present invention: in step S2, the heating temperature during heating and evaporation is 80-100°C, and the heating time is 2-3h, preferably 90°C and 2.5h.
[0033] Beneficial effects of the present invention:
[0034] (1) The present invention adds silicon carbide modified by zirconium boride to the fiber. After the zirconium boride and silicon carbide are combined, the crystal faces of the zirconium boride and the crystal faces of the silicon carbide are adsorbed together. Since the amount of silicon carbide used is greater than the amount of zirconium boride, silicon carbide crystals are adsorbed on multiple crystal faces of a zirconium boride crystal. In other words, silicon carbide will not completely surround multiple faces of zirconium boride, thereby forming a modified silicon carbide filled with zirconium boride. When the tube blank needs to be calcined during the process of preparing the ceramic filter tube, the silicon carbide is first oxidized on the surface of the zirconium boride to form a glass Membrane, as the temperature rises, the glass membrane spreads to the surrounding under the action of ductility. At this time, the edges of the glass membrane formed by multiple silicon carbide crystals on the zirconium boride crystal surface are connected to each other, thus forming a completely closed glass membrane sealing layer. At this time, zirconium oxide is isolated inside the glass membrane sealing layer. Even if the calcination temperature reaches above 1100°C, it will not contact the external environment, so it can avoid oxidation, thereby retaining its performance. Therefore, the modified silicon carbide can still have high-strength mechanical properties under harsh high-temperature environments, which is beneficial to improve the bending strength of the ceramic filter tube.
[0035] (2) In the preparation of ceramic filter tube fibers, the present invention first mixes carbon black with polypropylene staple fibers. The porous structure of the polypropylene staple fibers provides them with a larger surface area, which increases the chance of contact with carbon black particles. When the carbon black particles contact the polypropylene fibers, due to the high surface energy of carbon black, they are easily attached to the fiber surface. At the same time, the polar groups on the surface of the polypropylene fibers can interact with the polar groups of the carbon black particles to form hydrogen bonds or van der Waals forces, thereby firmly adsorbing the carbon black on the fiber surface. This adsorption effect enables the polypropylene staple fibers to form a wrapping layer around the carbon black particles. On the one hand, it can improve the binding force between the polypropylene fibers and the carbon black molecules. On the other hand, it is beneficial to disperse the carbon black molecules and avoid the problem of self-aggregation of the carbon black molecules to cause agglomeration. The chemical resistance, wear resistance, high temperature resistance, oxidation resistance and gas phase stability of carbon black itself can be fully exerted under the carrier of the polypropylene staple fibers.
[0036] (3) The present invention adds a small amount of organic fiber to the inorganic fiber. Alumina fiber and silica fiber are polycrystalline inorganic fibers, and polypropylene staple fiber is an organic fiber with orderly molecular chains. After the alumina fiber, silica fiber and polypropylene fiber are mixed, the alumina fiber and silica fiber are staggered, and the polypropylene fiber is inserted in the gap between the alumina fiber and the silica fiber. During high-temperature sintering, the alumina fiber and silica fiber expand first and then shrink during cooling. At the same time, the polypropylene fiber is burned out, thereby generating multiple interconnected pores. The carbon black inside the pores adheres to the inner wall of the pores after the polypropylene staple fibers are burned out, thereby enhancing the adsorption effect of the pores. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The present invention will be further described below in conjunction with the accompanying drawings.
[0038] Figure 1 This is a microscopic schematic diagram of the ceramic filter tube fiber obtained in Example 2 of the present invention magnified 100 times. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] Add 100 ml of dimethylamide to the mixer, heat the dimethylamide to 60°C, then add 20 g of silicon carbide to the mixer, stir at a speed of 2000 r / min for 20 min, then add sodium hydroxide dropwise to the mixer until the pH value reaches 7; then grind 6 g of zirconium boride into powder in a grinder, add the mixture to the mixer, stir at a speed of 1500 r / min for 2 h, then transfer to a distillation pot, distill at 160°C for 2 h, and there are block solids remaining in the distillation pot. The block solids are crushed and transferred to a grinder to be ground into powder to obtain 24.43 g of modified silicon carbide.
[0042] Example 2
[0043] 2g of carbon black and 3g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300r / min for 25min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 35g of alumina fibers, and 35g of silicon oxide fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, agate was used as a mixing ball, and the ball-to-material ratio was 1:2. Mixed fibers were obtained after ball milling for 6.5h. The mixed fibers were transferred to a beaker, and 2g of modified silicon carbide obtained in Example 1 was added to the beaker. After stirring evenly, the mixture was transferred to a drying oven and heated at 90°C for 2.5h to obtain a powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass cup, and 5g of paraffin was added to the glass cup. Finally, the glass cup was placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers. The microscopic schematic diagram of the fiber after being magnified 100 times by a Hitachi SU3500 scanning electron microscope is shown as follows Figure 1 shown.
[0044] Example 3
[0045] 2g of carbon black and 4g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300r / min for 25min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 37g of alumina fibers, and 37g of silicon oxide fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, and agate was used as a mixing ball with a ball-to-material ratio of 1:2. Mixed fibers were obtained after ball milling for 6.5h. The mixed fibers were transferred to a beaker, and 3g of modified silicon carbide obtained in Example 1 was added to the beaker. After stirring evenly, the mixture was transferred to a drying oven and heated at 90°C for 2.5h to obtain a powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass, and 6g of paraffin was added to the glass. Finally, the glass was placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0046] Example 4
[0047] 3g of carbon black and 5g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300r / min for 25min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 38g of alumina fibers, and 38g of silicon oxide fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, and agate was used as a mixing ball with a ball-to-material ratio of 1:2. Mixed fibers were obtained after ball milling for 6.5h. The mixed fibers were transferred to a beaker, and 4g of modified silicon carbide obtained in Example 1 was added to the beaker. After stirring evenly, the mixture was transferred to a drying oven and heated at 90°C for 2.5h to obtain a powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass, and 7g of paraffin was added to the glass. Finally, the glass was placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0048] Example 5
[0049] 4 g of carbon black and 6 g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300 r / min for 25 min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 40 g of alumina fibers, and 40 g of silicon oxide fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, and agate was used as a mixing ball with a ball-to-material ratio of 1:2. Mixed fibers were obtained after ball milling for 6.5 h. The mixed fibers were transferred to a beaker, and 4 g of modified silicon carbide obtained in Example 1 was added to the beaker. After stirring evenly, the mixture was transferred to a drying oven and heated at 90° C. for 2.5 h to obtain a powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass, and 8 g of paraffin was added to the glass. Finally, the glass was placed in a water bath and heated to 90° C. in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0050] Example 6
[0051] 5g of carbon black and 6g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300r / min for 25min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 42g of alumina fibers, and 42g of silicon oxide fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, and agate was used as a mixing ball with a ball-to-material ratio of 1:2. Mixed fibers were obtained after ball milling for 6.5h. The mixed fibers were transferred to a beaker, and 5g of modified silicon carbide obtained in Example 1 was added to the beaker. After stirring evenly, the mixture was transferred to a drying oven and heated at 90°C for 2.5h to obtain a powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass, and 10g of paraffin was added to the glass. Finally, the glass was placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0052] Comparative Example 1
[0053] 3g of polypropylene staple fiber, 35g of alumina fiber and 35g of silicon oxide fiber are added into a ball mill together, and then anhydrous ethanol is added into the ball mill as a medium, agate is used as a mixing ball, and the ball-to-material ratio is 1:2. After ball milling for 6.5h, mixed fibers are obtained, which are transferred into a beaker, and then 2g of modified silicon carbide obtained in Example 1 is added into the beaker. After stirring evenly, the mixture is transferred into a drying oven and heated at 90°C for 2.5h to obtain a powder. The powder is transferred into a grinder and ground into fiber powder. The fiber powder is transferred into a glass cup, and then 5g of paraffin is added into the glass cup. Finally, the glass cup is placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0054] Comparative Example 2
[0055] Compared with Example 2, the only difference is that the modified silicon carbide prepared in Example 1 is replaced by silicon carbide.
[0056] Comparative Example 3
[0057] Compared with Example 2, the only difference is that the modified silicon carbide prepared in Example 1 is replaced by zirconium boride.
[0058] Comparative Example 4
[0059] 2g of carbon black and 3g of polypropylene staple fibers were added to a crushing mixer and mixed at a speed of 2300r / min for 25min to obtain carbon black-polypropylene staple fibers. The carbon black-polypropylene staple fibers, 35g of alumina fibers, and 35g of silica fibers were added to a ball mill together. Anhydrous ethanol was added to the ball mill as a medium, and agate was used as a mixing ball with a ball-to-material ratio of 1:2. Mixed fibers were obtained after ball milling for 6.5h. The mixed fibers were transferred to a drying oven and heated at 90°C for 2.5h to obtain powder. The powder was transferred to a grinder and ground into fiber powder. The fiber powder was transferred to a glass cup, and 5g of paraffin was added to the glass cup. Finally, the glass cup was placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fibers.
[0060] Comparative Example 5
[0061] Add 3g of polypropylene staple fiber, 35g of alumina fiber and 35g of silica fiber into a ball mill, add anhydrous ethanol as the medium, use agate as the mixing ball, and the ball-to-material ratio is 1:2. After ball milling for 6.5h, mixed fiber is obtained. The mixed fiber is transferred to a drying oven and heated at 90°C for 2.5h to obtain powder. The powder is transferred to a grinder and ground into fiber powder. The fiber powder is transferred to a glass cup, and 5g of paraffin is added to the glass cup. Finally, the glass cup is placed in a water bath and heated to 90°C in a water bath and stirred evenly to obtain ceramic filter tube fiber.
[0062] The ceramic filter tube fibers obtained in Examples 2-6 and Comparative Examples 1-5 were respectively made into filter tube samples by hot pressing and sintering method, and then performance testing was carried out. The method for making the filter tube is as follows: a double-station wax pressing machine is used to press the ceramic core blank, the mold temperature is 25°C, the slurry temperature of the ceramic filter tube fiber is 90°C, and the tube body sample of Φ20mm×Φ15mm×40mm is pressed under an injection pressure of 4MPa. The pressure holding time is 10s, and the pressed tube body sample is calcined at 1200°C for 2h, and the filter tube sample can be obtained after cooling.
[0063] The filter tube samples prepared by using the ceramic filter tube fibers prepared in Examples 2-6 and Comparative Examples 1-5 were tested for performance, and the test items included apparent porosity and flexural strength. The test method was as follows:
[0064] Apparent porosity: Archimedes drainage method was used;
[0065] Bending strength: Use WDW-50 microcomputer-controlled electronic universal testing machine.
[0066] The test results are listed in Table 1. Table 1 is as follows:
[0067] Table 1
[0068]
[0069]
[0070] By analyzing the data in Table 1, it can be seen that the ceramic filter tube obtained by using the ceramic filter tube fibers prepared in Examples 2-6 has a higher apparent porosity and stronger bending strength than that of Comparative Examples 1-5.
[0071] In Comparative Example 1, both the apparent porosity and the flexural strength decreased. This may be because carbon black was not added, resulting in the carbon black no longer being wrapped inside the polypropylene fiber. The volume of the polypropylene molecules dispersed in the fiber mixture was reduced, and therefore the pores produced after burning became smaller, thereby reducing the apparent porosity. At the same time, the elimination of carbon black also caused the obtained ceramic fiber to lose the properties carried by the carbon black itself, so the flexural strength was also reduced.
[0072] In Comparative Example 2, both the apparent porosity and the flexural strength decreased. This may be because zirconium boride was not used to modify silicon carbide, resulting in the inability to exert the performance of zirconium boride. In Comparative Example 3, both the apparent porosity and the flexural strength decreased. This may be because silicon carbide was not used to protect zirconium boride, resulting in the zirconium boride being oxidized and losing its performance during the subsequent calcination process. In Comparative Example 4, both the apparent porosity and the flexural strength decreased. This may be because the modified silicon carbide was cancelled. In Comparative Example 5, both the apparent porosity and the flexural strength decreased. This may be because both carbon black and modified silicon carbide were cancelled, resulting in their inability to exert their performance.
[0073] In the description of the present invention, it should be understood that the terms "upper", "lower", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, and a specific direction structure and operation, and therefore, cannot be understood as a limitation of the present invention. In addition, "first" and "second" are only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.
[0074] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0075] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A ceramic filter tube fiber, characterized in that: The invention is composed of the following raw materials in parts by weight: 35-42 parts of alumina fiber, 35-42 parts of silicon oxide fiber, 3-6 parts of polypropylene short fiber, 2-5 parts of carbon black, 2-5 parts of modified silicon carbide, and 5-10 parts of plasticizer; Wherein, the modified silicon carbide is composed of silicon carbide and zirconium boride in a mass ratio of 5:(1-2); The preparation method of the modified silicon carbide is: Step 1: Add silicon carbide to dimethylformamide at 55-65°C and stir evenly to obtain a silicon carbide solution, and add sodium hydroxide dropwise to the silicon carbide solution to adjust the pH to 6.8-7.2; Step 2: Grind the zirconium boride into powder and add it into the silicon carbide solution with high-speed stirring, and distill it under stirring, and finally grind it into powdery modified silicon carbide.
2. The ceramic filter tube fiber according to claim 1, characterized in that: In the first step, the ratio of silicon carbide to dimethylamide is 1 g: (3-5) ml.
3. The ceramic filter tube fiber according to claim 1, characterized in that: In the second step, the stirring rate of the high-speed stirring is 1500-2000 r / min, and the stirring time is 1.5-2 h.
4. The ceramic filter tube fiber according to claim 1, characterized in that: In the second step, the distillation temperature is controlled at 150-170°C.
5. The ceramic filter tube fiber according to claim 1, characterized in that: The plasticizer is a mixture of one or more of paraffin, dibutyl phthalate and triethyl citrate.
6. A method for preparing the ceramic filter tube fiber according to any one of claims 1 to 5, characterized in that: Follow these steps in order: S1: mixing carbon black and polypropylene short fibers uniformly under high-speed stirring to obtain carbon black-polypropylene short fibers, adding the carbon black-polypropylene short fibers, alumina fibers, and silica fibers into a ball mill, and then adding anhydrous ethanol into the ball mill to mix the materials to obtain mixed fibers; S2: Add modified silicon carbide to the mixed fiber and mix evenly, then heat and evaporate to dryness and grind to obtain fiber powder, add plasticizer to the fiber powder and stir evenly at 80-100° C. to obtain ceramic filter tube fiber.
7. The method for preparing ceramic filter tube fibers according to claim 6, characterized in that: In the step S1, the carbon black and the polypropylene short fibers are stirred at a rotation speed of 2000-2500 r / min for 20-30 min to obtain the carbon black-polypropylene short fibers.
8. The method for preparing ceramic filter tube fibers according to claim 6, characterized in that: In the step S1, the mass ratio of balls to materials in the ball mill is 1:(1.5-2), and the mixing time is 6-7 hours.
9. The method for preparing ceramic filter tube fibers according to claim 6, characterized in that: In the step S2, the heating temperature during heating and evaporation is 80-100°C, and the heating time is 2-3h.
Citation Information
Patent Citations
ZrB2 / SiC composite powder special for thermal spraying ceramic coating and preparation method of ZrB2 / SiC composite powder
CN106316402A
High-temperature-resistant ceramic fiber tube
CN109665764A